Pendampingan Reference Manager Bagi Guru SD Negeri Sumur Welut Iii/440 Surabaya - Feny Rita Fiantika; Suryaman Suryaman; Triman Juniarso; Amelia Widya Hanindita; Cholifah Tur Rosidah (STMIK Royal, 2023)
This community service activity is used to assist teachers in citing scientific work. This activity is based on the needs of teachers at SDN Sumur Welut III Surabaya who do manual citations of scientific articles so that they do not show consistency of citations. The reference manager training used in community service is Mendeley's application. Participants in this activity were 20 teachers at SDN Sumur Welut III Surabaya with a series of mentoring activities for creating accounts and installing Mendeley, installing Plugins for Microsoft Office Word, installing Plugins for Web Browsers, using the Mendeley application, adding references from files , adding manual references, adding references from Web Browsers, changing reference details, adding citations to documents, adding references, adding citation styles, and changing citation styles. It can be concluded that this mentoring activity makes a good contribution to teacher professionalism in utilizing reference managers when writing scientific papers, this is evidenced by the teacher's ability to use reference managers of more than 95% in the minimal category quite well.Keywords: mendeley; reference manager; teacher competency. Abstrak: Pengabdian kepada masyarakat dilakukan untuk membantu guru agar dapat mensitasi karya ilmiah. Kegiatan ini didasarkan pada kebutuhan para guru di sekolah sasaran yang masih menggunakan sitasi karya ilmiah secara manual sehingga tidak memperhatikan konsistensi pengutipan. Pendampingan reference manager yang diajarkan melalui kegiatan pengabdian kepada masyarakat berupa aplikasi mendeley. Peserta pendampingan adalah para guru di SDN Sumur Welut III Surabaya sebanyak 20 orang dengan rangkaian kegiatan pembimbingan mendaftarkan akun, menginstalisasi Mendeley, menginstal plugin untuk Microsoft Word, menginstal plugin untuk Web Browser, mempraktikkan penggunaan perangkat lunak Mendeley, menginput referensi dari arsip file, menginput referensi manual, menginput referensi dari Web Browser, mengganti detail referensi, menginput kutipan pada dokumen, menginput daftar pustaka, menginput gaya pengutipan, dan mengganti gaya pengutipan. Berdasarkan hasil kegiatan pendampingan, dapat memberikan kontribusi yang baik kepada profesionalitas guru dalam memanfaatkan reference manager saat menulis karya ilmiah. Hal ini terbukti dengan kemampuan guru dalam menggunakan reference manager lebih dari 95% dalam kategori minimal cukup baik.Kata kunci: mendeley; reference manager; kompetensi guru.